Klinische Entscheidungsfindung bei der Behandlung des diabetischen Makulaödems mit DEX-Implantat: ein Konsenspapier - Augustin, Albert J.; Feltgen, Nicolas; Haritoglou, Christos; Hoerauf, Hans; Maier, Mathias M.; Mardin, Christian Y.; Schargus, Marc (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Currently two intravitreally applied corticosteroids (dexamethasone and fluocinolone) are licensed in Germany for treatment of diabetic macular oedema (DME). The use of DEX implant for DME in daily clinical practice has not been defined in detail. Following a Delphi panel survey, a group of retina experts set out to come up with a consensus for use of the DEX implant in DME. Material and Methods International and national treatment recommendations were identified from the literature. A steering group generated a catalogue of 72 statements on the aetiology and pathogenesis of DME, therapy with DEX implant, use of DEX implant in patients previously treated with VEGF-inhibitors, use of DEX implant in combination therapy, safety of DME therapies as well as patientsÊ burden of treatment. Twenty-Two ophthalmologists from private practice and 6 hospital ophthalmologists participated in the Delphi panel via Survey Monkey. Consensus was reached if at least 75% of participants agreed or disagreed with a statement. Statements for which consensus was not reached were discussed once more during the expert consensus meeting and a vote was taken. Based on these results a treatment algorithm for foveal DME was proposed. Results If a patient does not show sufficient response after 3â Š-â Š6 months of anti-VEGF treatment (visual acuity gain of < 5Â ETDRS letters or reduction of central retinal thickness ≤ 20%), a switch to DEX implant should take place. DEX implant is also suitable in eyes with longer presentation of DME, showing e.g. massive lipid exudates. DEX implant is suitable as first-line therapy especially in pseudophakic patients, patients unwilling or able to comply with tight anti-VEGF injection intervals or patients with known vascular diseases. With fixed control visits every 4â Š-â Š8 weeks, use of DEX implant is flexible and individual. Decision parameters for repeated use should be visual acuity, retinal thickness and intraocular pressure. Treatment of both eyes on the same day should not take place. Conclusion The algorithm presented reflects survey as well as expert discussion results and may differ from recommendations issued by the German professional society. The consensus recommendations for the treatment of DME generated during the survey and meeting of retina experts are intended to guide use of DEX implant in daily practice.
CRIS-Team Scopus Importer:2021-02-12
Keywords: clinical practice; Delphi consensus; DEX implant; diabetic macular edema; treatment algorithm